50 A Measurable Clinical Pathway for Atrial Fibrillation: What are the Benefits for Patients, Clinicians, Commissioners and Cardiac Networks?. (3rd June 2016) - Callaghan, Stephen; Mills, Joseph; Taylor, Bruce; O'Connor, Wendy
Abstract : Introduction: The Strategic Clinical Network CM SCN has developed a unique clinical pathway for atrial fibrillation (AF) as part of a 3 phase approach to improve outcomes for people with AF or at risk of AF. Phases 1 and 2: promotion of NICE guidance (with audit review) on anticoagulation (AC) and education and support to primary care are complete. The pathway includes key process and outcome measures based on best practice and guidance. This facilitates robust clinical management of AF and reduces associated morbidity and mortality. Clinicians, providers, cardiac networks and commissioning organisations can now measure the validity and effectiveness of clinical interventions across the full pathway of AF-related care in addition to promoting effective collaborative working. Methods: The CM SCN identified and brought together an expert panel of clinicians and managers to create the pathway. The experience of the expert panel ranged from public health, primary, secondary and tertiary care and included specialists from general practice, general cardiology, nursing, pharmacy, electrophysiology and interventionists. An independent external facilitator (funded by Boehringer Ingelheim) managed the process and delivered the pathway on time. The pathway was developed by email (Delphi technique) and required three half day meetings. Process and outcome measures were agreed by both clinicians and managers. Aims of the pathway are: Prevention of atrial fibrillation, early detection of atrial fibrillation, treatment of atrial fibrillation in acute and long-term settings, reduction of complications and support at the end of life. There are four sections to the pathway 1) Screening 2) Identification and assessment of AF 3) Initial management 4) Long-term management. Each section contains a flow chart, key points on the purpose, importance and consequence of each section, specific notes on each section and a table with indicators, standards, guidelines and competencies. Conclusion: We have shown that it is possible within nine months to produce a comprehensive pathway for people with AF that is measurable, fits within the current NHS landscape and maximises clinicians and managers time effectively. We have educated over 100 clinicians in the use of the pathway to date. We anticipate the this pathway will increase the detection of AF, increase in the number of people with AF treated with effective and appropriate AC, reduce the number of people with AF related stroke and increase support to clinicians, providers and commissioning organisations. We are currently evaluating this pathway over a 24 month period at both general practice and network level using GRASP-AF, CHA2 DS2 -VASc and other KPIs within the pathway. We anticipate that this pathway will benefit all professional stakeholders involved in AF care but more importantly, improve outcomes for people with AF.